Pengaruh ESG (Environmental, Social, and Governance) terhadap Tingkat Profitabilitas Perusahaan (Studi Empiris pada Sektor Energi yang Terdaftar di BEI Periode 2018–2022) - Tariyu, Mahung Silobabalo Siru (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine the effect of Environmental, Social, and Governance disclosure on the profitability level of energy-sector companies listed on the Indonesia Stock Exchange during the 2018–2022 period. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample was selected using purposive sampling and consisted of 12 companies, resulting in 60 firm-year observations. Data were analyzed using panel data regression with EViews 12. The results show that Environmental disclosure, Social disclosure, and Governance disclosure do not have significant effects on profitability as measured by Return on Assets. Simultaneously, the three ESG disclosure dimensions have a significant effect on profitability, although the explanatory power of the model remains low. A robustness test using Return on Equity as an alternative profitability proxy shows that Environmental and Social disclosure remain insignificant, while Governance disclosure has a significant effect. These findings indicate that ESG disclosure in Indonesian energy-sector companies has not yet become a dominant factor in explaining profitability, partly because ESG disclosure is still developing and may still be treated as supplementary information by stakeholders.